2020
DOI: 10.1113/jp279909
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 expressed throughout the arterial circulation regulates vasoconstriction and blood pressure

Abstract: Key points  The functional roles of the capsaicin receptor, TRPV1, outside of sensory nerves are unclear. We mapped TRPV1 in the mouse circulation, revealing extensive expression in the smooth muscle of resistance arterioles supplying skeletal muscle, heart and adipose tissue.  Activation of TRPV1 in vascular myocytes constricted arteries, reduced coronary flow in isolated hearts and increased systemic blood pressure. These functional effects were retained after sensory nerve ablation, indicating specific sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 59 publications
(152 reference statements)
2
58
0
3
Order By: Relevance
“…permeability through TRPV1 activated by high concentrations of capsaicin is sufficient to constrict arterioles (Phan et al, 2020). Here we found that nifedipine completely inhibits myogenic tone, negating a contribution of Ca 2+ entry through TRPV1.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…permeability through TRPV1 activated by high concentrations of capsaicin is sufficient to constrict arterioles (Phan et al, 2020). Here we found that nifedipine completely inhibits myogenic tone, negating a contribution of Ca 2+ entry through TRPV1.…”
Section: Discussionsupporting
confidence: 50%
“…Recently, we performed functional mapping of TRPV1 throughout the mouse circulation. This analysis revealed extensive TRPV1 expression in the vascular smooth muscle of arterioles in the skeletal muscle, heart and adipose tissues (Phan et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations